Physicians' Letters to their Patients: A Reflection Exercise for Graduating Medical Students - Alison Clay; Elizabeth Ross; Saumil Chudgar; Colleen Grochowski; Dan Shapiro (Association of American Medical Colleges, 2015)
Abstract Introduction The emotional and psychological costs of frontline medicine can be profound. This small-group session uses letters written by practicing physicians to prepare rising first-year residents to examine the toll of medical mistakes, problems in hierarchy, witnessing tragedy, and other issues. Methods This workshop is a 2-hour small-group discussion session led by faculty. Students participate in groups of about eight students with one faculty facilitator per group. Students have 15 minutes to write to a patient about an unresolved issue. They then share either their letter or a sample letter written by another physician. The group discusses the impacts these events have on the students as providers and ways to appropriately deal with emotions without putting themselves at risk for burnout. Results Students were required to complete an anonymous evaluation within 48 hours of the completion of the exercise. We report evaluation data from 96 students who participated in this workshop in 2014. More than 90% thought the session should be mandatory the following year, and over 80% stated that it resulted in significant individual reflection. Comments from students indicated that the session normalized their experiences and allowed them to move forward as they were starting their residency. Discussion We have implemented this session for the past 8 years at the Duke University School of Medicine with graduating fourth-year medical students. Themes frequently encountered in students' letters include regret for care provided, the difficulty students have in witnessing suffering, and gratitude towards patients and their families for the learning experiences.